2016
DOI: 10.1007/s10508-016-0782-7
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Investigation Comparing Psychosocial and Physical Sexual Experiences Related to Alcohol and Marijuana Use among Adults

Abstract: Alcohol and marijuana are two of the most prevalent psychoactive substances and each may result in distinct psychosocial and physical sexual experiences and different sexual risk behaviors. With marijuana becoming more accepted in the US along with more liberal state-level policies, it is important to examine and compare users’ psychosocial and physical sexual experiences and sexual risk behavior associated with these drugs. In this study, we interviewed 24 adults who recently used marijuana before sex. Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 34 publications
1
41
0
Order By: Relevance
“…Three themes were constructed from the data. The first theme indicated that drug-taking changes a person's sexual norms (Bourne, Reid, Hickson, Torres-Rueda, & Weatherburn, 2014;Claire Van Hout & Brennan, 2011;Deimel et al, 2016;Eiserman, Diamond, & Schensul, 2005;El-Bassel, Gilbert, & Rajah, 2003;Green & Halkitis, 2006;Jerome, Halkitis, & Siconolfi, 2009;Jessell et al, 2017;Lim, Akbar, Wickersham, Kamarulzaman, & Altice, 2018;Liu & Chai, 2018;Lorvick et al, 2012;McElrath, 2005;Mullens, Young, Hamernik, & Dunne, 2009;Palamar, Acosta, Ompad, & Friedman, 2018;Palamar, Kiang, Storholm, & Halkitis, 2014;Skårner & Svensson, 2013). This theme contained two subthemes: (a) acute drug-taking increases a person's perceived sexual autonomy, and, (b) people who consume drugs are perceived as "sexually available".…”
Section: Resultsmentioning
confidence: 99%
“…Three themes were constructed from the data. The first theme indicated that drug-taking changes a person's sexual norms (Bourne, Reid, Hickson, Torres-Rueda, & Weatherburn, 2014;Claire Van Hout & Brennan, 2011;Deimel et al, 2016;Eiserman, Diamond, & Schensul, 2005;El-Bassel, Gilbert, & Rajah, 2003;Green & Halkitis, 2006;Jerome, Halkitis, & Siconolfi, 2009;Jessell et al, 2017;Lim, Akbar, Wickersham, Kamarulzaman, & Altice, 2018;Liu & Chai, 2018;Lorvick et al, 2012;McElrath, 2005;Mullens, Young, Hamernik, & Dunne, 2009;Palamar, Acosta, Ompad, & Friedman, 2018;Palamar, Kiang, Storholm, & Halkitis, 2014;Skårner & Svensson, 2013). This theme contained two subthemes: (a) acute drug-taking increases a person's perceived sexual autonomy, and, (b) people who consume drugs are perceived as "sexually available".…”
Section: Resultsmentioning
confidence: 99%
“…Alcohol use is typically associated with social outgoingness, and alcohol consumption is commonly associated with meeting random sexual partners and having unplanned sex [49]. A recent study reported that compared to marijuana, alcohol use was more likely to lead to atypical partner choices or post-sex regret [50]. Given the potential negative effects of alcohol on sexual behaviors, future HIV prevention and harm reduction programs should consider patterns of alcohol use, especially those living with HIV, to increase their awareness of the sexual risks associated with alcohol use and to guide them toward making safer sexual decisions.…”
Section: Discussionmentioning
confidence: 99%
“…In one qualitative study examining substance use and sexual experiences among young adults, alcohol was commonly used by young men for pursuing potential sexual partners, and young women reported being more accepting of sexual offers from men when using alcohol [42]. In contrast, when using cannabis, young women reported being more selective regarding sexual partners.…”
Section: Cannabis Use In Intimate Relationshipsmentioning
confidence: 99%
“…Women and men who used cannabis prior to a sexual experience reported greater post-sexual satisfaction compared to those who used alcohol before sex, while participants who drank alcohol reported greater regret following sex. Some participants reported that the illegal nature of cannabis occasionally meant more private use that sometimes facilitated sexual encounters [42].…”
Section: Cannabis Use In Intimate Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation